The perspective of progressive poetry and the intellectual similarity of Faiz and Faraz - Mukhtar Ahmad; Dr. Muhammad Khawar Nawazish; Dr. Muhammad Sajid Khan (Zaban-o-Adab, 2021)
The progressive movement is the only ideological movement in Urdu literature and the ideology which is said to be the source of this movement was Marxism. Progressive Urdu writers made their pens the voice of the oppressed and exploited class of India. Not only that, but he also presented his specific views against colonialism in a broader perspective. The poetry of Faiz Ahmad Faiz, Makhdoom Mohi-ud-Din, Ali Sardar Jafari, Ahmad Nadeem Qasmi and Ahmad Faraz can be considered as representative of the presentation of progressive thought but interestingly, each writer had his own style of expression. Makhdoom and Ali Sardar Jafari do not speak the way Faiz speaks, the style of Ahmad Nadeem Qasmi is not that of Ahmad Faraz. But among the five poets mentioned above, the two who have more similarities in terms of thought and art are Faiz Ahmed Faiz and Ahmed Faraz. This research paper focuses on the intellectual similarities between Faiz and Faraz and their presentation.